Components of the protein-excretion apparatus of Pseudomonas aeruginosa are processed by the type IV prepilin peptidase. - Nunn, D N (1992)
In the Gram-negative pathogen Pseudomonas aeruginosa, mutants in the gene for the prepilin peptidase (pilD) are pleiotropic, as they not only fail to process pilin but also accumulate in the periplasm, in their mature form, several toxins and hydrolytic enzymes that are normally exported to the external medium (excreted). We have suggested that this excretion defect is due to the lack of PilD-dependent processing of proteins that share sequences in common with the prepilin subunit and that are components of a protein-excretion machinery. In this paper we report the isolation and characterization of transposon-induced excretion mutants with phenotypes similar to that of a pilD gene mutant. Using oligonucleotide probes designed to recognize sequences encoding the cleavage site of the type IV prepilins, we have isolated four linked genes with the predicted putative PilD-dependent cleavage site. Site-specific mutations within these genes have shown that they are required for protein excretion, and PilD-dependent processing of at least one of the four encoded proteins was demonstrated. Evidence suggests that similar components play a role in protein excretion in a wide variety of Gram-negative bacteria.